A framework on addressing climate change adaptation and vulnerabilities - Thornton, Philip K. (Academic Foundation, 2011)
The impacts of climate change spares no one. But the marginalised sectors and regions are projected to be hit the most with their limited capacities and resources to respond to climate change impacts, hence, increasing their vulnerability. A basic and urgent concern therefore is to know varying views about vulnerability as various approaches entail different diagnoses of a problem and different cures.